Study of the effect of a heterocyclic ring end group and an azomethane linkage on mesomorphism. (2nd July 2016) - Maheta, R. H.; Bhoya, U. C.
ABSTRACT: A novel homologous series RO-C6 H4 -COO-C6 H4 -N = CH-C5 H4 N of liquid crystalline Schiff base esters has been synthesized and studied with a view to correlating molecular structure to the liquid crystal properties on the basis of molecular rigidity and flexibility. All 12 members of series are either monotropic (C1, C3, C5 ) or enantiotropic (C2, C4, C6 to C16 ) nematic with the absence of smectogenic character throughout the series. Transition temperatures and LC behavior of the series were determined using an optical polarizing microscope equipped with a heating stage. Transition curves (Cr-N or Cr-I and N-I or I-N) behave in the normal established manner as depicted in a phase diagram. An odd–even effect is exhibited by the N-I transition curve up to the C8 homologue.